Aspergillosis in the Quail (Coturnix japonica) - Natasha Natasha; Erina Erina; M. Hasan (Jurnal Medika Veterinaria, 2022)
This study aimed to isolate and identify fungus that causes aspergillosis in the quail (Coturnix japonica). The samples used in this study were 30 pairs quail lungs taken randomly from the Hanin Group Quail Farm, Garot village, Darul Imarah subdistrict, Aceh Besar regency. The growth of the fungus was observed for Aspergillus sp. macroscopically and microscopically. The data were analyzed descriptively. The results of this study revealed that from 30 pairs quail lungs, Aspergillus sp. can be isolated from 26 out of 30 lungs. It can be concluded that 86.67% of the lung samples were infected with Aspergillus sp.